Inhibition of mesenchymal drift as a strategy for rejuvenation - de Lima Camillo, Lucas Paulo (Frontiers in Pharmacology, 2025)
Mesenchymal drift (MD), the progressive acquisition of mesenchymal traits by epithelial and endothelial cells, has emerged as a unifying mechanism of aging. Transcriptomic analyses across human tissues reveal that mesenchymal programs intensify with age and predict morbidity and mortality. By eroding lineage identity and promoting fibrosis, MD disrupts organ integrity in the lung, liver, kidney, heart, and brain. Mechanistically, it converges with epigenetic erosion, chronic inflammation, and extracellular matrix stiffening to establish self-reinforcing loops of dysfunction. Interventions that restore cellular identity can suppress MD: transient reprogramming resets epigenetic age and reduces fibrotic signatures without loss of identity, while chemical cocktails achieve similar rejuvenation effects with enhanced translational potential. Together, these findings establish MD as a tentative hallmark of aging and suggest that its inhibition could represent a strategy for cellular and tissue rejuvenation.